PICIS: Program Keluarga untuk Melatih Berpikir Kritis Keputusan Finansial Remaja di Era Digital - Novi Istina; Benny Setiawan (Universitas Pendidikan Ganesha, 2026)
Our adolescents today live in a digital ecosystem that allows them to conduct financial transactions without limits of space and time. Online games, e-wallets, and shopping platforms have become part of their daily lives. A recent viral case of an elementary school student who spent hundreds of thousands of rupiah on online game vouchers—triggering parental anger toward the cashier—illustrates how children’s financial decisions can occur rapidly, without time to pause and think, and without adequate parental guidance. Various studies also show that low financial literacy, the ease of cashless payments, and massive digital promotion contribute to impulsive buying behavior among adolescents. This article aims to describe the concept of PICIS as a simple family-based program to stimulate critical thinking skills in financial decision-making among adolescents aged 12–18 years. The method used is a literature review on critical thinking, adolescent financial literacy, and digital consumption behavior, combined with the design of a home-based program grounded in reflective practice. The review formulates the PICIS steps, which include: *Pahami dulu* (Understand first), *Informasi lengkap* (Gather complete information), *Cek konsekuensi* (Check the consequences), *Izin hati dan orang tua* (Seek inner and parental approval), and *Sikapi dengan bijak* (Respond wisely). Each step is mapped onto components of critical thinking, namely organizing information, analyzing options, evaluating consequences, and using information to make more responsible decisions. It is concluded that PICIS has the potential to become a practical framework for parents to transform “wanting to shop” moments into opportunities to practice critical financial thinking, while also opening avenues for future research to empirically test the effectiveness of this program. Keywords: critical thinking; adolescent financial literacy; digital financial decision-making; family program; digital consumption